Communication in youth mental health clinical encounters: Introducing the agential stance. (October 2022) - Bergen, Clara; Bortolotti, Lisa; Tallent, Katherine; Broome, Matthew; Larkin, Michael; Temple, Rachel; Fadashe, Catherine; Lee, Carmen; Lim, Michele C.; McCabe, Rose
When young people seek support from mental health care practitioners, the encounters may affect the young people's sense of self, and in particular undermine their sense of agency. For this study, an interdisciplinary team of academics and young people collaboratively analysed video-recorded encounters between young people and mental healthcare practitioners in emergency services. They identified five communication techniques that practitioners can use to avoid undermining the young person's sense of agency in the clinical encounter. They conceptualise the use of those techniques as the adoption of an agential stance towards the young person. The agential stance consists of: (a) validating the young person's experiences, (b) legitimising the young person's choice to seek help, (c) refraining from objectifying the young person, (d) affirming the young person's capacity to contribute to positive change, and (e) involving the young person in the decision-making process.